Peran Pemerintah Dalam Pengentasan Kemiskanan di Sumatera Utara - Delvia Irene Teresia Sihaloho; Widia Suryantina Nainggolan; Artha Nauli Sitohang (Outline Journal of Economic Studies, 2025)
Poverty is a completely limited situation that occurs not at the will of the person concerned. A population is said to be poor if it is marked by a low level of education, productivity employment, income, health and nutrition as well as welfare, which shows a circle of powerlessness. The most lagging province in Sumatra is North Sumatra. According to the Central Statistics Agency, there will be 1,356,720 poor people in North Sumatra in 2020. In terms of poverty, North Sumatra ranks fourth out of 34 Indonesian provinces according to the Central Statistics Agency in 2020, after East Java, West Java and Central Java, as can be seen in the chart below. By using qualitative research techniques, the main data used in this research is converted into secondary data from various sources. Direct Cash Assistance (BLt), NonCash Food Assistance (Bpnt), and Social Assistance are all based on Law no. Project 5 was implemented by the Regional Government of Medan City in 2015. These include housing assistance and a Business School.